'n Sosiaal-sielkundige perspektief oor kerkvereniging in die Nederduitse-Gereformeerde kerkfamilie: 'n kruiskulturele ondersoek - Jonck, Petronella (University of the Free State, 2005)
After ten years of democracy there is still hope that one denomination for the Family of th e Dutch Reformed Churches can be achieved. At the moment the process has just about come to a standstill and it is threatening to disintegrate. According to estimation only one of these kinds of studies has been done. This was done from a Theological inste ad of a Social-Psychological point of view. The aims of this study were achieved by gathering data from ‘n number of respondents in the different denominations of the Family of Dutch Reformed Churches in the Mangaung area. Six churches from the Dutch Reformed Churches N=104 (46, 6%), as well as the United Reformed Church N=47 (21, 1%) were used and the remainder of the respondents came from five Dutch Reformed Churches in Africa N=72 (32, 3%). A Biographical questionnaire as well as the Attitude towards Church Unification Scale was used. The influence of different variables such as language, gender, age, marital status as well as church activities on the attitudes of church members towards church unification was investigated. Multivariate Tests of Significan ce was used. Statistical analysis concluded that members of all the different denominations of the Dutch Reformed churches had a positive attitude towards church unification throughout the different denominations. The variable found to have the greatest in fluence on the attitude of church members was language. The other variables did not yield statistical significant differences toward church unification. It is one of the strangest twists of logic that it sometimes seems as if the Christian faith are used as the strongest tool to divide rather to bring together and reconcile people onto Jesus. In this study two research questions were posed. Firstly, what are members of the Dutch Reformed Family of Churches’ attitude towards church unification? Secondly, are there statistical significant differences between members of the Dutch Reformed Family of Churches’ attitude toward church unification regarding home language, level of education as well as monthly income? A total of 223 respondents were included which consisted of 104 (46,6%) Dutch Reformed Church members, 72 (32,3%) DRC in Africa members and 47 (21,1%) Uniting Reformed Church members. The Attitude towards Church Unification Questionnaire was utilized. Statistical analysis concluded that members of the Dutch Reformed Churches’ had a positive attitude towards church unification throughout the different denominations. The variable found to have the greatest influence on the attitude of church members was home language. Monthly income of the household was also significant on the 5% level, while level of education were not found to have a statistical significant influence on people’s attitude towards church unification.

Na tien jaar van demokrasie is daar steeds hoop dat een denominasie vir die Nederduits - Gereformeerde Kerkfamilie bereik kan word. Tans het die proses nagenoeg tot stilstand gekom en dreig om te verbrokkel . Na beraming is daar tot op hede slegs een so ‘n studie in hierdie verband onderneem en is uitgevoer vanuit ‘n Teologiese en nie ‘n Sosiaal - Sielkundige oogpunt nie. Die doelwitte van die studie is bereik deur inligting van verskeie respondente, afkomstig van die verskillende kerkverbande in die N.G. Kerkfamilie in die Mangaung – area, te bekom. Ses N.G. Kerke N=104 (46, 6%), asook Verenigende Gereformeerde Kerke N=47 (21, 1%) is by die ondersoek betrek. Die oorblywende respondente was afkomstig van vyf N.G. Kerke in Afrika N=72 (32, 3%). Sowel ‘n Biografiese vraelys as die Houding teenoor Kerkvereniging – Skaal is gebruik. Die invloed van verskillende veranderlikes, naamlik huistaal, geslag, ouderdom, huwelikstatus asook kerklike betrokkenheid op lidmate se hou ding teenoor kerkvereniging is ondersoek. Meerveranderlike variansie - ontledings is toegepas. Statistiese ontleding het beslis dat lede van die N.G. Kerkfamilie deurgaans ‘n positiewe houding teenoor kerkvereniging huldig. Daar is verder gevind dat huistaal die grootste invloed op kerklidmate se houding teenoor kerkvereniging uitgeoefen het. Die ander veranderlikes het nie statisties – beduidende verskille opgelewer nie.
Dissertation (M.Soc.Sc. (Psychology))--University of the Free State, 2005
Keywords: Church union -- Nederduitse Gereformeerde Kerk -- 20th century; South Africa -- Religion; Church -- Unity; Separate development; Belhar confession; Home language; Gender; Age; Church activities; Apartheid; Attitude; Church unification